Comparison of bladder ultrasonographic and rigid cystoscopic findings in patients with hematuria - Mehrdad Mostafalo; Naser Ghaemiyam; Karimollah Hajian-Tilaki; Emadodin Moudi (Babol University of Medical Sciences, 2019)
Background: Bladder cancer ranks ninth in world-wide cancer incidence and is 2.5-4 times more common in men, and painless gross hematuria is its typical clinical symptom. Cystoscopy is used to evaluate the cause of hematuria in bladder while the use and reliability of ultrasonography is questionable for this purpose. Therefore, the aim of this study was to compare abdominal ultrasonography and rigid cystoscopy in the diagnosis of bladder tumors in Babol Shahid Beheshti Hospital. Methods: In this cross-sectional study, 60 patients who were candidate for cystoscopy referred to Babol Shahid Beheshti Hospital in Iran in 2017-2018. In this study, rigid cystoscope was used to view the bladder after doing sonography. The numbers, demographic information (age, gender and residence) and clinical characteristics (indication of cystoscopy, history of chronic disease, sonographic and cystoscopic results) of patients were recorded in the checklist. Results: The mean age of patients (37 (61.7%)=males) was 58.65±14.26 (19-85) years and 48 (80%) of them were >50 years old. The sensitivity and specificity of sonography was 71.43 (95% CI: 29.4, 96.33) and 96.23% (95% CI: 87.02, 99.54) in detecting bladder tumors, respectively. The negative predictive and positive predictive values in sonography were 96.23 (95% CI: 88.76, 98.8) and 71.43% (95% CI: 37.25, 91.33) respectively. Conclusion: The results of this study indicate that since sonography has high negative predictive values in evaluating hematuria; therefore it can be replaced with rigid cystoscopy for patients with lower risk of malignancy.